Evaluating psychometric determinants of willingness to adopt sexual health patient portal services among black college students: A mixed-methods approach. Issue 2 (17th February 2021) - Jackman, Kevon-Mark P.; Hightow-Weidman, Lisa; Poteat, Tonia; Wirtz, Andrea L.; Kane, Jeremy C.; Baral, Stefan D.
Abstract: Objectives: To describe, using mixed-methods, perceptions of access to sexually transmitted infection test results via electronic personal health record (PHR) and correlates of willingness to adopt its use. Participants: Students at a mid-Atlantic historically black college. Methods: Focus-groups and interviews were conducted to explore themes on sexual health-related PHR-use ( N = 35). Codes were operationalized into survey measures assessing beliefs in a cross-sectional sample ( N = 354). Exploratory factor analysis identified latent factors among survey items. Multiple logistic regression models measured correlates of adoption willingness. Results: Three qualitative themes emerged on relative advantages, barriers, and functionality of PHRs. 57.6% of survey participants were willing to use PHRs for sexual health services. Reliable latent factors, centering on PHR convenience and functionality, were positively associated with adoption willingness. Conclusions : Data highlights interest among black college-age youth in adopting PHRs for comprehensive sexual health-related services. Adoption may be boosted with tailored designs responsive to expressed service needs.